2004
DOI: 10.4049/jimmunol.172.9.5588
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mitogen-Activated Protein Kinase Activity and TNF-α Production Associated with Mycobacterium smegmatis- but Not Mycobacterium avium-Infected Macrophages Requires Prolonged Stimulation of the Calmodulin/Calmodulin Kinase and Cyclic AMP/Protein Kinase A Pathways

Abstract: Previous studies have shown the mitogen-activated protein kinases (MAPKs) to be activated in macrophages upon infection with Mycobacterium, and that expression of TNF-α and inducible NO synthase by infected macrophages was dependent on MAPK activation. Additional analysis demonstrated a diminished activation of p38 and extracellular signal-regulated kinase (ERK)1/2 in macrophages infected with pathogenic strains of Mycobacterium avium compared with infections with the fast-growing, nonpathogenic Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
100
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 55 publications
4
100
3
Order By: Relevance
“…Emerging evidence suggests that IL-10 and TNF-␣ cytokines in macrophages are regulated upstream mainly by the p38 MAPK and ERK1/2 (11,62,63,92) signaling cascades. Although ERK1/2 activation is mainly required for TNF-␣ production (63,66), IL-10 induction is predominantly dependent on p38 MAPK signaling (60,65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that IL-10 and TNF-␣ cytokines in macrophages are regulated upstream mainly by the p38 MAPK and ERK1/2 (11,62,63,92) signaling cascades. Although ERK1/2 activation is mainly required for TNF-␣ production (63,66), IL-10 induction is predominantly dependent on p38 MAPK signaling (60,65).…”
Section: Discussionmentioning
confidence: 99%
“…Although ERK1/2 activation is mainly required for TNF-␣ production (63,66), IL-10 induction is predominantly dependent on p38 MAPK signaling (60,65). Accordingly, we have observed that internalization of Mtbhsp60 through TLR2 is associated with an increased phosphorylation of p38 MAPK, whereas engagement of this protein with TLR4 induced predominantly ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and Cultivation of Bone Marrow-derived Macrophages-Bone marrow-derived macrophages (BMM⌽s) were harvested from the bone marrow of 6-to 8-week-old C57BL/6 mice as described previously (26). Mature macrophages were harvested and stored at Ϫ140°C.…”
Section: Methodsmentioning
confidence: 99%
“…For Western blots, 10 g of native and deacetylated total lipid and purified GPLs were exposed to 3 ϫ 10 5 BMM⌽s for 4 h. BMM⌽s were then washed with icecold phosphate-buffered saline and treated for 10 min with icecold lysis buffer as previously described (26). Equal amounts of protein as determined by the MicroBCA protein assay (Pierce) were analyzed by Western blot for phosphorylated and total p38 and phosphorylated and total p65 NFB (21).…”
Section: Methodsmentioning
confidence: 99%
“…The relative production of TNF varies among pathogenic and nonpathogenic mycobacterial species (6). Regulation of TNF biosynthesis is complex.…”
mentioning
confidence: 99%